2021
DOI: 10.3389/fpls.2021.730737
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Physiological, and Photosynthetic Responses of Xanthoceras sorbifolium Bunge Seedlings Under Various Degrees of Salinity

Abstract: Xanthoceras sorbifolium Bunge is priced for its medical and energetic values. The species also plays a key role in stabilizing ecologically fragile areas exposed to excess soil salinity. In this study, the effects of salinity on the growth, physiological, and photosynthetic parameters of X. sorbifolium Bunge were investigated. The X. sorbifolium seedlings were subjected to five salt treatments: 0 (control, CK), 70, 140, 210, and 280 mM of sodium chloride (NaCl) solutions. NaCl caused a decrease in plant height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Under salt stress, the proline content increased significantly in the current study. The present findings are consistent with previous research on Brassica species [ 44 ], Phaseolus vulgaris [ 72 ], and Xanthoceras sorbifoliu [ 65 ], which revealed an increase in proline content under salt stress. The enhancement of the proline content might be due to increased activity of the pyrroline-5-carboxylate synthase (P5CS) of the proline biosynthetic pathway in Hibiscus cannabinus under salt stress.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Under salt stress, the proline content increased significantly in the current study. The present findings are consistent with previous research on Brassica species [ 44 ], Phaseolus vulgaris [ 72 ], and Xanthoceras sorbifoliu [ 65 ], which revealed an increase in proline content under salt stress. The enhancement of the proline content might be due to increased activity of the pyrroline-5-carboxylate synthase (P5CS) of the proline biosynthetic pathway in Hibiscus cannabinus under salt stress.…”
Section: Discussionsupporting
confidence: 93%
“…Soil salinization is now a major environmental threat to the long-term growth of global agriculture. It induces alterations in many physiological and metabolic processes, eventually reducing the crop yield, depending on the severity and duration of the stress [ 64 , 65 ]. Plants can tolerate or avoid saline conditions [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, native I. pseudacorus plants tended to show lower SLA, but higher leaf N concentrations than alien plants in the introduced range, and higher numbers of senescent leaves per sprout with increasing salinity. Previous studies have recorded an increase in salt tolerance related to ion accumulation in senescent leaf tissue (Reddy et al, 2017) and increased SLA (Grewell et al, 2021; Zong et al, 2021). In contrast, alien plants, exposed to similar soil salinities as the native plants, also had decreased LWC and LER with increasing salinity gradient, but responded with about half the decrease in these leaf traits than observed for native plants.…”
Section: Discussionmentioning
confidence: 96%
“…Apart from the ecological functions and excellent resistant ability, X. sorbifolium also has valuable seeds, from which the oil extracted can be used to produce high-quality healthcare products, since the component in the oil is potentially effective for the treatment of Alzheimer’s disease, rheumatism, gout, and learning and memory impairment ( Ji et al, 2017 ; Wu et al, 2018 ; Li et al, 2020 ). In our previous study, it was found that X. sorbifolium Bunge could cope with the salt stress by osmotic, enzyme, and photosynthesis regulations, which could effectively alleviate the damage caused by saline treatment ( Zong et al, 2021 ). Wang et al also investigated the physiological changes and molecular mechanisms underlying the responses of X. sorbifolium to salt and saline-alkali stress ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%